The Effect of Giving Cherry (Muntingia calabura) Leaf Extract on Tobacco Mosaic Virus (TMV) Attacks on Cayenne Pepper Plants (Capsicum frutescens L.) - Salsabilla, Alyara Oktavia; Martosudiro, Mintarto; Choliq, Fery Abdul (Journal of Tropical Plant Protection, 2024)
Cayenne pepper (Capsicum frutescens L.) is a horticultural crop that is widely cultivated in Indonesia and has high economic value. However, it is not uncommon for the cultivation process to encounter several obstacles, one of which is caused by the Tobacco Mosaic Virus (TMV). One of the actions that can be taken to control this disease is to use induction agents derived from plant extracts. The plants that can be used as inducers are cherry plants (Muntingia calabura). However, research on the use of cherry leaf extract is rarely applied, especially against the TMV virus.  Thus, this research needs to be conducted to determine the effect of cherry leaf extract on TMV attack on cayenne pepper plants. The study used a completely randomized design (CRD) in vivo with 6 treatments and 4 replications. The treatment given was cherry leaf extract with different application frequencies at a concentration of 5%. Parameters observed included the disease incubation period, disease intensity, plant growth, and assessment of plant resistance. The results showed that applying cherry leaf extract with an application frequency of 4 times extended the incubation period of TMV and reduced the intensity of TMV disease, with values of 17.88 days after inoculation and 11.20%, respectively. This treatment resulted in a plant resistance category of "resistant." Additionally, the application of cherry leaf extract 4 times also had a positive effect on plant growth, specifically plant height and number of leaves.